MAP OF THE LANDSCAPE UNITS AND GEOMORPHOSITES OF MONTE ARCI (SARDINIA) - Di Gregorio , Felice; Piras, Giuseppe (Alpine and Mediterranean Quaternary, 2005)
F. Di Gregorio & G. Piras, Map of the landscape units and geomorphosites of Monte Arci (Sardinia). (IT ISSN 0394-3356,2005).In the present paper a geomorphosites map is presented in which these sites are inserted in Landscape Units. The study area is thevolcanic complex of Monte Arci in Central-West Sardinia.By means of a detailed geomorphological mapping, performed with the aid of photo-interpretation and direct surveys in the field, different types of landscapes have been identified, according to their specific lithological, morphological and evolutive characteristics,that also have determined different types of landuse.It has been possible to distinguish the Landscape System of the Pliocene volcanites of Monte Arci that has been further subdivided inthe following Landscape Units:- Landscape Unit of the acid lava’s;- Landscape Unit of the intermediate lava’s;- Landscape Unit of the alkaline trachites;- Landscape Unit of the basic lava’s.The eastern flank is substantially very different and is characterised by the Landscape System of the marine Miocene sedimentarydeposits and the intra-Miocene volcanites, with recurrent rounded hills in marly-sandy terrains with discontinuous and sporadic outcropping of infrasedimentary volcanic products mostly in relief.The Western flank instead is characterised by the Landscape System of the continental plio-quaternary sedimentary deposits, with flatand downhill landforms such as glacis and alluvial mostly inactive cones.Inside each of these Landscape Units several géomorphosites have been identified, mapped and classified according to their genesis,all with own specific scientific, didactic and cultural-tourist interests.This type of analysis and cartographic representation allows to comprise inside these fundamental reference units (Landscape Unitsand Systems) single punctual geomorphologic elements, showing their genesis in a better way, their spatial distribution and densityand the possible relation with their surrounding environment. This kind of Map constitutes a valid basic information that allows to evaluate the potential experience of the landscape as a fundamental instrument of knowledge in the territorial and landscape planning and in Environmental Impact Assessment Studies.